The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1590/s0100-879x1999001000014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of policosanol on cerebral ischemia in Mongolian gerbils

Abstract: Policosanol is a mixture of higher aliphatic primary alcohols isolated from sugar cane wax, whose main component is octacosanol. An inhibitory effect of policosanol on platelet aggregation and cerebral ischemia in animal models has been reported. Thus, the objective of the present study was to evaluate the effect of policosanol on cerebral ischemia induced by unilateral carotid ligation and bilateral clamping and recirculation in Mongolian gerbils. Policosanol (200 mg/kg) administered immediately after unilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 29 publications
(26 reference statements)
0
20
0
Order By: Relevance
“…No demonstration of the mechanisms of the antiplatelet effects of policosanol is available, but they involve a simultaneous decrease of TxA 2 and increase of prostacyclin concentrations rather than an inhibition of COX 2 activity [13,15], being logical to expect a greater antiplatelet efficacy of poli + AS over pla + AS therapy. We also found that poli + AS reduced low-density lipoprotein-cholesterol (LDL-C) by 16.7% (week 12) and 25.5% (week 24) as compared to pla + AS, and that also had benefits on total cholesterol and HDL-C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No demonstration of the mechanisms of the antiplatelet effects of policosanol is available, but they involve a simultaneous decrease of TxA 2 and increase of prostacyclin concentrations rather than an inhibition of COX 2 activity [13,15], being logical to expect a greater antiplatelet efficacy of poli + AS over pla + AS therapy. We also found that poli + AS reduced low-density lipoprotein-cholesterol (LDL-C) by 16.7% (week 12) and 25.5% (week 24) as compared to pla + AS, and that also had benefits on total cholesterol and HDL-C.…”
Section: Discussionmentioning
confidence: 99%
“…Policosanol, a mixture of 8 high molecular weight sugarcane wax alcohols, has reduced platelet aggregation in experimental and clinical studies [9][10][11][12][13]. Also, policosanol has shown protective effects in experimental brain ischemia models, and to increase the antiplatelet/antithrombotic effects of AS [14,15], and long-term administered prevented the progression of carotid-vertebral atherosclerosis in humans [16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a few short-term studies indicated that the cholesterol-lowering effect of policosanol was better than that of statins such as simvastatin, pravastatin, lovastatin, probucol, or acipimox and with fewer side effects in patients with type II HC [27][28][29][30]. Prat et al [31], Crespo et al [32] and Noa et al [33] reported that policosanol reduces intermittent claudication [27,34], platelet aggregation [35,36], diastolic blood pressure [DBP] and systolic blood pressure [SBP] [37,38] in older patients with hypertension and type II HC and dyslipidemia in type 2 DM [27,39]; and cerebral ischemia in animals [40]. Policosanol decreased progression and increased regression of CVD as assessed by thallium-labeled myocardial perfusion scintigraphy (TL-MPS) and Doppler-ultrasound, and decreased symptoms of CVD [41][42][43].…”
Section: Essential Alcohols: Policosanolmentioning
confidence: 99%
“…Additionally, Policosanol showed a protective effect on the myocardial necrosis induced by isoprenaline in a rat experimental model [34] . Results of another study proved an antiischemic effect of policosanol administered after induction of cerebral ischemia, in two different experimental models in Mongolian gerbils, suggesting a possible therapeutic effect in cerebral vascular disorders [35] . The effects of octacosanol mentioned above made a foundation for the present study design since the reaction mediated by reactive oxygen species was the common feature of those pathological changes including PD.…”
Section: Discussionmentioning
confidence: 92%